Understanding Skin Screening Practices among Children at Elevated Risk for Melanoma to Inform Interventions for Melanoma Prevention and Control - Parsons, Bridget G. (J Cancer Educ, 2020)
BACKGROUND: Melanoma is the deadliest form of skin cancer. Screening can aid in early disease detection, when treatment is more effective. Although there are currently no consensus guidelines regarding skin screening for pediatric populations with elevated familial risk for melanoma, at-risk children with the help of their parents and healthcare providers, may implement skin self-exams. Healthcare providers may also recommend screening practices for these children. The goal of the current study was to describe current screening behaviors and provider recommendation for screening among children of melanoma survivors. METHODS: Parents of children with a family history of melanoma completed a questionnaire that included items on children’s screening frequency, thoroughness, and who performed the screening. RESULTS: Seventy-four percent of parents reported that their children (mean age=9.0 years, SD=4.8) had engaged in parent-assisted skin self-exams (SSE) in the past six months. Only 12% of parents reported that children received SSEs once per month (the recommended frequency for adult melanoma survivors). In open-ended responses, parents reported that healthcare providers had provided recommendations around how to conduct SSEs, but most parents did not report receiving information on recommended SSE frequency. Twenty-six percent of parents (n=18) reported that children had received a skin exam by a healthcare provider in the past six months. CONCLUSIONS: The majority of children with a family history of melanoma are reportedly engaging in skin exams despite the lack of guidelines on screening in this population. Future melanoma preventive interventions should consider providing families guidance about implementing screening with their children.